2022
DOI: 10.1371/journal.pone.0273687
|View full text |Cite
|
Sign up to set email alerts
|

“The vaccination is positive; I don’t think it’s the panacea”: A qualitative study on COVID-19 vaccine attitudes among ethnically diverse healthcare workers in the United Kingdom

Abstract: Background Globally, healthcare workers (HCWs) were prioritised for receiving vaccinations against the coronavirus disease-2019 (COVID-19). Previous research has shown disparities in COVID-19 vaccination uptake among HCWs based on ethnicity, job role, sex, age, and deprivation. However, vaccine attitudes underpinning these variations and factors influencing these attitudes are yet to be fully explored. Methods We conducted a qualitative study with 164 HCWs from different ethnicities, sexes, job roles, migrat… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
22
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(26 citation statements)
references
References 27 publications
2
22
0
Order By: Relevance
“…A study in the eastern Australian state of Queensland identified that participants' belief that close family and friends would want them to get vaccinated was significantly associated with uptake [28]. While we did not explore this directly, we saw mutuality flowing in the other direction: our participants felt that those closest to them would get vaccinated, and some were actively encouraging this, as also seen in HCWs in other global settings [24,26]. We note that "normal" for our participants was a world free from pandemic control measures which were successfully keeping the disease out of the community, whereas HCWs in countries such as the UK embraced vaccination as a way out of the pandemic because other prevention and control measures had failed [29].…”
Section: Discussionmentioning
confidence: 76%
See 2 more Smart Citations
“…A study in the eastern Australian state of Queensland identified that participants' belief that close family and friends would want them to get vaccinated was significantly associated with uptake [28]. While we did not explore this directly, we saw mutuality flowing in the other direction: our participants felt that those closest to them would get vaccinated, and some were actively encouraging this, as also seen in HCWs in other global settings [24,26]. We note that "normal" for our participants was a world free from pandemic control measures which were successfully keeping the disease out of the community, whereas HCWs in countries such as the UK embraced vaccination as a way out of the pandemic because other prevention and control measures had failed [29].…”
Section: Discussionmentioning
confidence: 76%
“…They trusted the data on COVID-19 vaccine safety and efficacy, which was not the case for HCWs in all comparable global settings (e.g. the UK's ethnically diverse health workforce [24] and health workers in Hong Kong [25]). Our participants felt confident that vaccination would protect themselves and others around them, enabling the community to get back to "normal."…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…Comparative data revealed strong social inequalities and discrimination against migrant HCWs and racialised groups in the HCWF. This was especially documented for BAME doctors in the UK (53,54,56,57,58,59,60) and ethnic minorities in Brazil (17,62,63).…”
Section: Intersectional Inequalities Of Migrant Hcws In Health System...mentioning
confidence: 87%
“…The category of passive acceptance includes respondents who had one or two doses of the vaccine, but still had doubts about its e cacy or safety. Declination of vaccine or passive acceptance has been identi ed more likely among ethnic minority communities and female healthcare workers (Gogoi, 2022).…”
Section: Research Background: Previous Research On Vaccine Hesitancymentioning
confidence: 99%